Determination of elemental impurities in valproic acid an epilepsy drug by using ICP-MS - Satish Ganta; T. Siva Rao; K. Rama Srinivas; Pallapati Suman (Journal of Trace Elements and Minerals, 2022)
Background: According to previously published research, different analytical methods (GC, HPLC, etc.) were used to determine Valproic acid and its Genotoxic impurities. The heavy metals were also attempted to be determined using the ICP-MS technique in other drug substances. Methods: The present work evaluated the 10 elemental impurities (Cd, Pb, As, Hg, Co, V, Ni, Fe, Al, and Sn) in Valproic acid by ICP-MS method utilising a microwave-assisted acid digestion process as there is no analytical method for the heavy metal analysis in Valproic acid. Results: The developed analytical method was selective, sensitive and rapid for capable of detecting heavy metal at 0.19 ppm As, 0.38ppm Hg, 0.06 ppm Pb, 0.06ppm Cd, 0.63 ppm Co, 1.25ppm V,2.5 ppm Ni, 25 ppm Fe, 25 ppm Al and 75 ppm Sn and further quantified from 0.375ppm As,0.75ppm Hg, 0.125 ppm Pb, 0.125ppm Cd, 1.25ppm Co, 2.5ppm V, 5 ppm Ni, 50 ppm Fe, 50ppm Al and 150 ppm Sn to 200 percent of limit concentration. The analytical method found to be linear with correlation coefficient > 0.99. The percentage recoveries of heavy metals at three different concentrations with spiking in samples of Valproic acid were achieved an acceptable range at 70% to 150 %. The method was precise and robust and its relative standard deviation was below 20%. The actual % RSD in precision are 1.0 % As, 0.5 % Hg, 0.5 % Pb, 1.2 % Cd,0.6 % Co, 0.6 % V, 0.6 % Ni, 0.5% Fe, 0.9 % Al and 0.3 % Sn. Conclusion: Heavy metal analysis by ICP-MS is a powerful technique, Therefore the developed method can use for routine quantitative determination of 10 elemental impurities in Valproic Acid.